Selecting and optimizing a reliable DNA extraction method for isolating viral DNA in okra (Abelmoschus esculentus) - Jeyaseelan, T. C.; Jeyaseelan, E. C.; De Costa, D. M.; Shaw, M. W. (Faculty of Science, University of Jaffna, 2019)
Detection and identification of viruses in okra plant is important to manage viral diseases. Good quality of DNA is essential for the PCR based detection and subsequent genomic sequencing. However, the DNA extraction has been greatly affected by mucilaginous substances present in okra plant parts. Objective of this study is to find out an extraction method that can eliminate mucilaginous materials and yield good quality DNA. Five different protocols were tested with okra leaf samples having okra yellow vein mosaic disease (OYVMD) symptoms. Quantity and purity of extracted DNA was tested using Nanodrop spectrophotometer. Precise quantity comparison was done by measuring total plant DNA in relation to the copy number of ACT2 gene using quantitative polymerase chain reaction (qPCR). The extracted DNA samples were used as template for detection of Bhendi yellow vein mosaic virus and Bhendi yellow vein mosaic betasatellite using specific primers. A modified protocol (modified method 1), introduced in this study, produced better yield and quality of DNA compared to other tested protocols. The method yielded 32 μg DNA for 100 mg leaf powder and the ratios A260/A280 and A260/A230 were 1.8 and 2.1, respectively. The qPCR quantification further confirmed higher quantity of DNA yield in this modified protocol. End point PCR with virus specific primers yielded very bright bands for Bhendi yellow vein mosaic virus and Bhendi yellow vein mosaic betasatellite. In conclusion, the modified method 1 can be used to extract good quality and quantity of DNA from okra.
Keywords: Okra; DNA extraction; Plant viruses